High‐Resolution Cytometry for High‐Content Cell Cycle Analysis. Issue 1 (1st October 2014) - Furia, Laura; Pelicci, Piergiuseppe; Faretta, Mario
Abstract: One of the major limitations of flow cytometry (FCM) is the absence of an intracellular view. Automated microscopy and image analysis, together with technological developments, led to new approaches in cytometry that bypass the above limitation, introducing high resolution, high content, and large statistical sampling. However, few attempts have been made, until now, to translate the wide repertoire of FCM assays into high‐content image screening. This unit describes the implementation of an acquisition and analysis protocol for evaluation of the cell cycle by automated microscopy. The approach grants the possibility to perform simultaneous analysis of a high number of different parameters. A large part of this unit is devoted to the description of hardware features that can optimize the recorded information together with the acquisition and analysis procedures employed to produce good‐quality data. Curr. Protoc. Cytom . 70:7.41.1‐7.41.15. © 2014 by John Wiley & Sons, Inc.